Signals of inclusion: how faculty demographics impact the use of identity safety cues in undergraduate STEM syllabi - Anthony Coutts; Crystal Brown; Francesca Bernardi (Frontiers in Education)
In this study we explore the relationship between faculty demographics such as gender, academic rank, and field, and the presence of Identity Safety Cues (ISCs) in undergraduate course syllabi. ISCs, such as the inclusion of instructor pronouns, inclusivity statements, and materials authored by women and gender minority scholars, are increasingly seen as indicators of inclusive teaching practices. Drawing from an original dataset of 163 syllabi from introductory undergraduate courses at Worcester Polytechnic Institute, a STEM-focused institution in the United States of America, we examine how these cues are used by faculty across different fields, gender, and rank. We employ a combination of descriptive and predictive statistics methods to investigate the influence of faculty demographics on syllabi design. Our findings reveal that women faculty across all disciplines are more likely to include ISCs compared to their male counterparts. Field also plays a substantial role in syllabi design, with faculty in the Humanities & Arts including ISCs much more frequently than those in STEM and the Social Sciences. The implications of these findings suggest a need for targeted faculty professional development and mentorship to promote better inclusive pedagogy in STEM education.